2017
DOI: 10.1177/2042753017731235
|View full text |Cite
|
Sign up to set email alerts
|

The nature of E-learning adoption by stakeholders of a university in Africa

Abstract: Studies looking at the nature of technology adoption from a multi-dimensional perspective have remained below expectation especially in African countries. This study, therefore, sought to explore the nature of e-learning adoption in the University of Ghana using a multi-stakeholder approach. A quantitative survey approach was adopted for this study. The three major categories of stakeholders (students, instructors and e-learning administrators) responded to a questionnaire on the nature of their engagement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…There is the need for critical examination of success factors, challenges, and theories from the perspective of the stakeholders (Snigdha and Pattnail, 2020). A multi-stakeholder approach needs to be utilized to study the nature of technology adoption (Ansong et al, 2017). Frequent information and brainstorming sessions should be organized for staff of the university who are involved in e-learning activities to solicit views on feasible ways of implementing e-learning, while being guided by policies.…”
Section: Discussionmentioning
confidence: 99%
“…There is the need for critical examination of success factors, challenges, and theories from the perspective of the stakeholders (Snigdha and Pattnail, 2020). A multi-stakeholder approach needs to be utilized to study the nature of technology adoption (Ansong et al, 2017). Frequent information and brainstorming sessions should be organized for staff of the university who are involved in e-learning activities to solicit views on feasible ways of implementing e-learning, while being guided by policies.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Ansong et al (2017) explored the nature of e-learning adoption in the University of Ghana using a multi-stakeholder approach. The analysis revealed that e-learning was yet to receive a university-wide adoption and again it was discovered that, the prevalent activity on the e-learning platform was "viewing marks and grades."…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Teachers and students start realizing the emerge of technology in learning is extremely essential in current educations [8], [14], [15]. However, the use of technology in the learning process might somehow questionable since numerous aspects such as the availability, support system, and digital literacy distinguish the quality of technological integration [11], [16], [17]. This research denoted results portraying the urgency of technology tools in learning and its possibility to foster learning goals.…”
Section: Introductionmentioning
confidence: 99%